Humor Bahasa Bugis dalam Interaksi Sosial Masyarakat di Desa Minangandala: Penelitian - Mardini Dg Parebbo; Salam; Sitti Rachmi Masie (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
Bugis language is language of communication, meaning that Bugis language is used to communicate between individuals who know the language. Bugis language has been known in the archipelago, because the Bugis people have immigrated to various places and have spread widely outside South Sulawesi. This study uses a qualitative research type, presentation of descriptive data in the form of words and santences written, or spoken from the observed humor speakers. Based on the results of the study, the researcher found that there were several humors in the Bugis language that were often used by people in everyday life. In the focus of the study, the forms of humor found were 3 forms, namely humor in the forms of satire, forms of humor in everyday life and funny hyperbolic humor. In the focus of the third study, the function, of humor found by the researcher was 4 functions, namely easing tension, there were 2 humors, teaching others to see problems from various angles, there were 2 humors, entertaining, there were 3 humors, making someone aware and making someone tolerate something, there were 2 humors.